Dampak Minat Generasi Muda dalam #Kaburajadulu terhadap Tren Migrasi Tenaga Kerja ke Luar Negeri - Mauliqs Ekky Dwi Astuty Misnan; Sulton; Ardhana Januar Mahardhani (CV. AKIRA JAVA BULU, 2025)
This study aims to explore the impact of young Indonesians’ growing interest in the #KaburAjaDulu movement on the trend of labor migration abroad. The hashtag, which has gained popularity across social media platforms, reflects the dissatisfaction of Generation Z with the socio-economic conditions in Indonesia and their desire to seek better opportunities overseas. This research employs a qualitative descriptive approach through a literature review method, analyzing scientific journals, government policy documents, academic articles, and credible online sources. The findings indicate three significant impacts of this trend: first, a rise in brain drain, where skilled young talents migrate abroad and potentially weaken national human capital; second, the emergence of digital migration, with youth pursuing remote careers as digital nomads in more supportive global ecosystems; and third, growing social dissonance among Indonesian youth, marked by ideological divisions between those who choose to stay and reform the system versus those who leave it. These impacts highlight a shift in values, aspirations, and strategies among the younger generation. The study concludes that while migration offers individual benefits, it poses long-term challenges to national development and social cohesion, and therefore, requires comprehensive policy responses and public awareness initiatives.